Estudio de Mediatizadores psicológicos para el disfrute de la sexualidad en jóvenes universitarios - Cedeño Acosta, Denise (Universidad Central “Marta Abreu” de Las Villas, 2010)
La presente investigación se realizó en la universidad Central Marta Abreu de las Villas con el tema “Estudio de mediatizadores psicológicos que inciden en el disfrute de la sexualidad en jóvenes universitarios”. Se realizó a partir de una metodología cuanti-cualitativa. La muestra la conformaron catorce jóvenes de diferentes especialidades. Entre ellos había siete con relaciones de pareja estable y siete con relaciones inestables. Los mediatizadores psicológicos que se estudiaron fueron: físico-corporal, verbal-emocional, conductual-emocional y extraverbal-paralingüístico. Los resultados obtenidos basados en el comportamiento de los mencionados mediatizadores psicológicos son muy variables, incluso dentro de un mismo grupo de estudio. Se pudo percibir como en personas donde primaban insatisfacciones en un mediatizador, repercutía negativamente en la percepción que tenían del disfrute de su sexualidad de forma general. Aún cuando las mayores insatisfacciones se centraron en el mediatizador físico-corporal, se apreció que éstas son secundarias a afectaciones en otro mediatizador, fundamentalmente en el verbal-emocional en el caso de los jóvenes con parejas estables y el conductual-emocional en los jóvenes con parejas inestables. Los resultados no variaron significativamente entre los grupos en cuanto al número de aparición mas al analizar los datos a profundidad se detectaron las diferencias a un mayor nivel.

The current research was realized on the Universidad Central “Marta Abreu” de las Villas and is named “Study of the psychological mediatizators wich measure, the sexuality enjoy of young universitaries”. The research was done based on a quanti-qualitative methodology. Four teen young of different specialities conform the sample. Between then were seven with stable couple, relations ships and seven with unstable relation ships. The psychological mediatizators studies studied were: corporal physique, emotional verbal, emotional behaviours, and paralinguistic extraverbal, the obtained results based on the mediatizators behaviour were variable, even inside the same study group. Was noted how the people in wich the unsatisfaction where in first place in a mediatizator, rebounded negatively in the perception they had about their sexuality enjoy in a general way. Even when the biggest unsatisfaction where centred in the corporal physique mediatizator was seen that these one secondaries to affections in other mediatizadtor, mainly the emotional verbal in the case of young with stable couple and the behaviour emotional in the young with unstable couples. The results did not make a remarkable variation between the groups in the case of number apparition, however when a deep analyse of data was made, comes out the difference at a higher level.The current research was realized on the Universidad Central “Marta Abreu” de las Villas and is named “Study of the psychological mediatizators wich measure, the sexuality enjoy of young universitaries”. The research was done based on a quanti-qualitative methodology. Four teen young of different specialities conform the sample. Between then were seven with stable couple, relations ships and seven with unstable relation ships. The psychological mediatizators studies studied were: corporal physique, emotional verbal, emotional behaviours, and paralinguistic extraverbal, the obtained results based on the mediatizators behaviour were variable, even inside the same study group. Was noted how the people in wich the unsatisfaction where in first place in a mediatizator, rebounded negatively in the perception they had about their sexuality enjoy in a general way. Even when the biggest unsatisfaction where centred in the corporal physique mediatizator was seen that these one secondaries to affections in other mediatizadtor, mainly the emotional verbal in the case of young with stable couple and the behaviour emotional in the young with unstable couples. The results did not make a remarkable variation between the groups in the case of number apparition, however when a deep analyse of data was made, comes out the difference at a higher level.
Keywords: Mediatizadores Psicológicos; Sexualidad; Sexuality; Jóvenes; Young Adult